Exploiting Short Stories in the EFL Classroom (Stamford Journal of English, 2013)
The purpose of this article is to focus on the effectiveness of using short stories in language instruction. Some instructors may think that teaching EFL is just to focus on linguistic benefits only and eventually their learners will communicate in the target language. On the other hand, instructors who have tried to accumulate literature in the curricula have observed that literary texts add a new dimension to the teaching of EFL. Short stories, for example, come to a great help for learners to learn the four skills-reading, writing, speaking and listening. In addition, with short stories, instructors can motivate learners to learn some literary aspects, cultural awareness and can make them think critically. However, before introducing the short stories instructors should realize the benefits of using this material and design their lessons that can meet the needs of their learners. DOI: http://dx.doi.org/10.3329/sje.v4i0.13493 Stamford Journal of English Vol.4 2008 pp.124-141